The increase in hemoglobin concentration with altitude varies among human populations - Gassmann, Max; Mairbäurl, Heimo; Livshits, Leonid; Seide, Svenja; Hackbusch, Matthes; Malczyk, Monika; Kraut, Simone; Gassmann, Norina N.; Weißmann, Norbert; Muckenthaler, Martina (Annals of the New York Academy of Sciences, 2019)
Decreased oxygen availability at high altitude requires physiological adjustments allowing for adequate tissue oxygenation. One such mechanism is a slow increase in the hemoglobin concentration ([Hb]) resulting in elevated [Hb] in high-altitude residents. Diagnosis of anemia at different altitudes requires reference values for [Hb]. Our aim was to establish such values based on published data of residents living at different altitudes by applying meta-analysis and multiple regressions. Results show that [Hb] is increased in all high-altitude residents. However, the magnitude of increase varies among the regions analyzed and among ethnic groups within a region. The highest increase was found in residents of the Andes (1 g/dL/1000 m), but this increment was smaller in all other regions of the world (0.6 g/dL/1000 m). While sufficient data exist for adult males and females showing that sex differences in [Hb] persist with altitude, data for infants, children, and pregnant women are incomplete preventing such analyses. Because WHO reference values were originally based on [Hb] of South American people, we conclude that individual reference values have to be defined for ethnic groups to reliably diagnose anemia and erythrocytosis in high-altitude residents. Future studies need to test their applicability for children of different ages and pregnant women.
Gesehen am 29.04.2020